Penentuan Logo, Merek, dan Kemasan Produk Wedang Uwuh Menggunakan Metode Focus Group Discussion (FGD): Penelitian - Leony Leony; Siwitri Munambar; Novia Aristi Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to design logos and brands limited to color, shape, and meaning using the Focus Group Discussion (FGD) method, which involves the owners and employees of P4S X in Kulon Progo Regency. This method was chosen to seek the opinions of business actors regarding packaging design that suits the character of the product and the desires of consumers. The research was conducted with a descriptive qualitative approach and was divided into two stages of FGD, namely the identification and evaluation stage of packaging design. The attributes discussed include the shape of the packaging, the color combination, the contents of the packaging, and the information that should be there. The results of the FGD show that the cultural identity and traditional values of wedang uwuh need to be reflected in the brand name, logo, and packaging of this product. An effective brand is one that is memorable and shows uniqueness and authenticity. Logos are supposed to display visual elements that represent the company's identity. Meanwhile, the ideal packaging is one that is practical, eco-friendly, and attractive. In addition, packaging design also needs information, such as composition, how to serve, and how to store so that consumers feel more confident to buy. The active participation of FGD participants also helps in designing logos, brands, and packaging that reinforce the product's identity as a traditional beverage